FROM PRIVATE TO PUBLIC: STUDENTS’ PERSPECTIVES ON SHIFTING TO ENGLISH MEDIUM EDUCATION IN NEPAL - Saud, Mohan Singh (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Nepal’s school education has public and private systems. Private schools are de facto English medium schools, while public schools have Nepali as a medium of instruction. However, some public schools have adopted English medium instruction, and this trend continues. In recent years, there has been a tendency for students studying in private schools to transfer to English medium public schools. In this scenario, this study explores the perspectives of the students shifting from private to English medium public schools in Nepal. This study, grounded in neoliberal ideology, adopted a phenomenological qualitative research design. Three students were purposively selected. The data were collected through unstructured interviews. The interviews were analyzed using a thematic approach. The results showed that the shift of students to English medium public schools for government-recognized certificates significantly reduced the financial burden on parents. The students found that learning in public schools with diverse learning environments was more meaningful. Both private and English-medium public schools used a dual medium of instruction (English-Nepali), with more English used in private schools. The study suggests that English-medium education in public schools in Nepal has attracted students away from English-medium private schools.